Evaluating Age-related Disparity of Outcomes in Ewing Sarcoma Patients Treated at a Pediatric Academic Medical Center. Issue 5 (July 2021) - Perisa, Michael P.; Stanek, Joseph; Setty, Bhuvana A.; Nicol, Kathleen; Yeager, Nicholas
Abstract : Adolescent and young adult (AYA) patients with Ewing sarcoma have inferior survival compared with pediatric patients even when treated with similar regimens. Investigation into specific explanations is lacking. A retrospective chart review of Ewing sarcoma patients at a single institution was performed, and 104 patients were identified, 45 were 15 to 39 years of age (AYA cohort) and 59 younger than 15 years (pediatric cohort). AYA patients demonstrated more metastatic disease (50% vs. 24%, P =0.009), peripheral tumor location (64% vs. 41%, P =0.025), percentage of male patients (76% vs. 51%; P =0.010), and tumor size ≥5 cm (93% vs. 70%, P =0.016) than pediatric patients. Five-year overall survival was 77.7% and 53.0% and event-free survival was 68.7% and 40.6% for pediatric versus AYA, respectively. Similar rates of toxicity and chemotherapeutic dose adjustments were demonstrated. In this cohort, increased AYA patient mortality appears to be related to disease characteristics rather than treatment-related differences.